2008
DOI: 10.1038/sc.2008.53
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of traumatic spinal cord injuries in Finland over a 30-year period

Abstract: Study design: Register survey. Objective: To provide national Finnish data on the incidence of traumatic spinal cord injury (TSCI) over a 30-year period. Setting: Käpylä Rehabilitation Centre, Helsinki, Finland. Methods: Patients aged 16 years and older who sustained a TSCI between 1976 and 2005 were identified using the registers of the Käpylä Rehabilitation Centre. Results: The medical records of a total of 1647 patients (1362 men and 285 women) were analyzed. The mean annual incidence rate for the entire po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
56
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 11 publications
20
56
3
4
Order By: Relevance
“…In Australia, O'Connor 3 showed the agestandardized SCI incidence rate for 14.5 per million persons in 1998/1999. Among European countries, the incidence rates were lower relativelyFnamely, 13.8 for Finland ), 4 13.1 for Ireland (2000), 5 12.7 for Turkey (1992) 6 and 19.4 for France (2000), 7 respectively. In developing countries, systematic epidemiological studies were relatively less.…”
Section: Introductionmentioning
confidence: 94%
“…In Australia, O'Connor 3 showed the agestandardized SCI incidence rate for 14.5 per million persons in 1998/1999. Among European countries, the incidence rates were lower relativelyFnamely, 13.8 for Finland ), 4 13.1 for Ireland (2000), 5 12.7 for Turkey (1992) 6 and 19.4 for France (2000), 7 respectively. In developing countries, systematic epidemiological studies were relatively less.…”
Section: Introductionmentioning
confidence: 94%
“…The gender distribution (men/women) of TSCI was 3.4/1, which was similar to other studies, and their gender distribution ranged from 3.0/1-4.8/1. 15,16 It could be explained by risk-taking behaviors men performed. The highest number for both male and female were in 31-45 and 46-60 age groups, whereas the peak age in other reports range from 15 to 30.…”
Section: Epidemiological Features Of Tsci Hf Wang Et Almentioning
confidence: 99%
“…[6][7][8] In Beijing, the 2002 sampling survey shows that the ratio of males to females was 3.11:1.ref. 3 In the current study, the gender ratio is 4.1:1, which also indicates that males account for the majority of TSCIs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that TSCI incidence per million population per year is 73.0 in Taiwan (2000)(2001)(2002)(2003), 15.0 in Australia (2007)(2008), 44.0 in Russia (1994)(1995)(1996), 13.8 in Finland (197613.8 in Finland ( -2005 and 40.0 in USA (2005). [3][4][5][6][7] It is estimated that the annual incidence in Beijing is 60.6 per million, 8 which is much higher than the reported figures for some other countries and regions. A 10-fold increase has occurred in Beijing compared with the rates from the 1980s (6.8 per million) to 2002 (60 per million).…”
Section: Introductionmentioning
confidence: 99%